2010
DOI: 10.1016/j.cancergencyto.2010.01.014
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent deletion of 9q34 in adult normal karyotype precursor B-cell acute lymphoblastic leukemia

Abstract: The prognosis of adult normal karyotype (NK) precursor B cell acute lymphoblastic leukemia (B-ALL) has not improved over the last decade mainly because separation into distinct molecular subsets has been lacking and no targeted treatments are available. We screened the genome of blasts from ten adult NK B-ALL patients for novel genomic alterations by array comparative genomic hybridization and verified our results with fluorescent in situ hybridization and gene expression profile using the same probes. The res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 20 publications
0
11
0
Order By: Relevance
“…It was reported that heterozygous depletion of Nup188 was found in three of 10 B-ALL patients. (24) It is important to investigate if reduced expression of Nup188 or mutations in the remaining allele might affect K-fiber stability and fidelity of chromosome segregation, leading cells to oncogenic transformation in these patients. Further study is required to elucidate the role of Nup188 on proper chromosome segregation and its relevance to cancer.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was reported that heterozygous depletion of Nup188 was found in three of 10 B-ALL patients. (24) It is important to investigate if reduced expression of Nup188 or mutations in the remaining allele might affect K-fiber stability and fidelity of chromosome segregation, leading cells to oncogenic transformation in these patients. Further study is required to elucidate the role of Nup188 on proper chromosome segregation and its relevance to cancer.…”
Section: Discussionmentioning
confidence: 99%
“…(23) Importantly, the NUP188 gene resides in the region (9q34) that is frequently deleted in adult B-cell acute lymphoblastic leukemia (B-ALL). (24) However, the pathological significance of this deletion and ⁄ or mutation remains unclear. Here, we addressed whether Nup188 has any function other than membrane transport and found that it plays an important role in mitosis.…”
mentioning
confidence: 99%
“…Recurrent deletion of 9q34 has been found in adult normal karyotype precursor B-cell ALL (26), although it is not a common finding, and the reported deleted region does not contain the WDR85 gene. DPH1, also named OVCA1, is ubiquitously expressed in normal human tissues (27).…”
Section: Discussionmentioning
confidence: 99%
“…However, the advantage of SNP arrays over aCGH is that SNP arrays can reveal CNN LOH [Tuna et al, 2009]. In ALL, genome-wide array studies have previously revealed submicroscopic alterations in pediatric cases [Irving et al, 2005;Kuiper et al, 2007;Mullighan et al, 2007;Kuchinskaya et al, 2008;Rabin et al, 2008;Bungaro et al, 2009], in cases from all ages [Strefford et al, 2007;Mullighan et al, 2008;Simons et al, 2011], and in adults [Matteucci et al, 2010;Nowak et al, 2010;Okamoto et al, 2010]. Regarding our ALL study, we detected several gene deletions, previously reported by others; BTG1 at 12q22 [Kuiper et al, 2007;Mullighan et al, 2007Mullighan et al, , 2008Okamoto et al, 2010;Lundin et al, 2012], BTLA at 3q13.2 [Mullighan et al, 2007], MLL at 11q23 [Harbott et al, 1998;Takeuchi et al,1999], as well as CDKN2A , CDKN2B , JAK2, and PAX5 at 9p [Irving et al, 2005;Kuiper et al, 2007;Mullighan et al, 2007;Usvasalo et al, 2010a].…”
Section: Discussionmentioning
confidence: 99%